Aplikasi Sistem Pakar Berbasis Instant Messenger Untuk Diagnosa Awal Penyakit Ginjal - Wahyu Rizki Arifianto; I Made Arsa Suyadnya; I Made Sudarma (Jurnal SPEKTRUM, 2018)
In Indonesia, the number of people who dead from suffered kidney disease has increasing. It’shappens because many people has less knowledge about the early symptoms of this disease. Kidney is one of the important organ in human body, which’s it performs to filtrating excess salt, water, and acid. Information technology utilization could be a great solution for this case. Build an expert system application based on instant messenger for early diagnose check of kidney disease is expect to do the initial diagnose process to be faster and could engage more people who curious about this disease. The system method that was used in this research is forward chaining method who based on multiplatforms using Telegram instant messanger application. This application could solves the problem which is it application can displaying the diagnosis result quickly and accurately based on the symptoms that will be asked by the system. In black box testing, this application has functions that have been successful. And based on the results of usabilty scale system testing (SUS), obtained ascore of 78 which means this application can run well on Telegram Messaging.